(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To compare preoperative quality of life (QoL) using the OQLQ between skeletal Class II and Class III patients indicated for orthognathic surgery. Methods: A cross-sectional study enrolled 50 adults (Class II n = 25, Class III n = 25). The 22-item OQLQ (4 domains, total 0–88) was administered preoperatively. Independent t-test or Mann-Whitney U test was used (p < 0.05). Results: Class III patients were younger (20.4 ± 2.2 vs. 25.7 ± 7.3 years; p = 0.002) and predominantly male (64.0% vs. 36.0%; p = 0.048). Total OQLQ scores did not differ significantly between groups (44.53 ± 14.81 vs. 40.51 ± 15.24; p = 0.349). Facial aesthetics scores were significantly higher in Class III (15.64 ± 3.82 vs. 12.82 ± 4.15; p = 0.016). No significant differences were found in other domains. Conclusion: Class II and Class III patients showed no significant difference in total preoperative OQLQ scores. However, Class III patients had higher facial aesthetics scores.